1998
DOI: 10.1016/s0022-5347(01)62379-6
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I/Ii Trial of Transurethral Surgery Combined With Concurrent Cisplatin, 5-Fluorouracil and Twice Daily Radiation Followed by Selective Bladder Preservation in Operable Patients With Muscle Invading Bladder Cancer

Abstract: This pilot study demonstrates a high rate of response to this combined chemotherapy/radiation regimen in conjunction with a visibly complete transurethral resection. Reevaluation after a short induction phase allows for the early selection of patients with persistent disease for radical cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…In a study by Erlangen and several others, responses were evaluated 4 to 6 weeks post-CRT by restaging TURBT (1-3). Conversely, according to the Massachusetts General Hospital (MGH) and Radiation Therapeutic Oncology Group (RTOG) protocols, response evaluation should be performed much earlier, i.e., after approximately 40 Gy of induction radiation therapy (20-22). In the literature, salvage cystectomy plays an important role in patients with a persistent tumor after CRT.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Erlangen and several others, responses were evaluated 4 to 6 weeks post-CRT by restaging TURBT (1-3). Conversely, according to the Massachusetts General Hospital (MGH) and Radiation Therapeutic Oncology Group (RTOG) protocols, response evaluation should be performed much earlier, i.e., after approximately 40 Gy of induction radiation therapy (20-22). In the literature, salvage cystectomy plays an important role in patients with a persistent tumor after CRT.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of local control of the disease as well as the significant toxicity that is associated with radiation therapy remains problematic [4][6]. To improve efficacy, several clinical trials on organ-sparing management were carried out to test the effects of combined chemotherapy and radiation [7], [8]. However despite numerous efforts, chemoradiation studies remain associated with suboptimal local control of disease and decrease survival compared with radical surgery.…”
Section: Introductionmentioning
confidence: 99%
“…23 However, a promising survival outcome, 56%-73% overall survival rate at 5 years, was reported in several phase II trials. 19,20,24 Chemoradiotherapy with cisplatin monotherapy has shown good tolerance in several reports. 11,18,25 Our study showed that carboplatin alone with radiotherapy provided excellent disease control and was well tolerated in frail or aged patients with bladder cancer.…”
Section: Yin-hsun Feng Et Almentioning
confidence: 99%